The enigma of cuboid diamonds: the causes of inverse distribution of optical centers within the growth zones - Vasilev,E.A.; Zedgenizov,D.A.; Klepikov,I.V. (Journal of Geosciences, 2020)
In the present work, diamonds with yellow cores and a slightly colored or colorless rims have been studied. Three groups of crystals that differ in spectroscopic features have been identified. In the crystals of the first group, the heterogeneity in color is due to the variation in nitrogen concentration, which is present as the simplest low-temperature nitrogen С center. Absorption spectra of the first group display peaks at wavenumbers 1344 and 1332 cm-1 of С and С+ centers, respectively. The second group also exhibits higher nitrogen concentrations in the form of C centers in the colored zone. However, the concentration of nitrogen in the form of high temperature А-centers, and the total nitrogen content is higher at the periphery of crystals. The FTIR absorption spectra of this group display both 1344 and 1332 cm-1 peaks. Crystals of the third group do not contain C centers. The 1332 cm-1 and the A center bands are observed in the FTIR absorption spectra. In the photoluminescence spectra of the colored zone of the third group, the bands S1 and S2 have been found and the doublet lines 883 and 885 nm of the simplest Ni-containing centers. Previously unobserved systems with zero-phonon lines at 799.5, 819.6, 869.5 and 930 nm lines have been registered in the photoluminescence spectra of the third group under 787 nm excitation. It is hereby proposed that this luminescence is due to Ni-containing centers. In the third group of crystals, Ni seems to stabilize C+ centers; and hence the coloring of crystal zones is consistent with Ni impurity distribution. Crystals of each group have distinct sources: the first group is from Yubileinaya pipe, the second group from the placers of North Yakutia with unknown primary sources and the third from the Uralian deposits.
Keywords: FTIR; photoluminescence; nitrogen; nickel